Feasibility of using FA and GGBS-derived geopolymer for high liquid limit soil stabilization - Li, Chenchen; Tan, Guohao; Weng, Hui; Shi, Jiachen; Li, Shixiang; Xie, Jianwei (Frontiers in Materials, 2025)
IntroductionTo improve the comprehensive utilization rate of industrial solid wastes, this study developed geopolymer materials using fly ash ground granulated blast furnace slag (GGBS), sodium silicate, and sodium hydroxide for the stabilization of high liquid limit soil.MethodA series of tests including compaction, unconfined compressive strength (UCS), California bearing ratio (CBR), resilient modulus, scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS) were conducted. The investigation focused on the influence of alkali activator modulus and dosage on the strength of geopolymers. Additionally, the impact of geopolymer dosage on the optimum moisture content (OMC), maximum dry density (MDD), UCS, CBR, and resilient modulus of stabilized soil was examined.Results and discussionThe results indicated that the OMC of the stabilized soil decreased while the MDD increased with increasing geopolymer dosage. The UCS of the stabilized soil significantly improved with the addition of geopolymer, achieving values of 0.52 MPa, 1.68 MPa, 3.25 MPa, and 4.18 MPa at 7 days for geopolymer dosages of 0%, 4%, 8%, and 12%, respectively. Similarly, the CBR of the stabilized soil increased with geopolymer dosage, reaching 1.2%, 3.5%, 6.5%, and 10.5% after 4 days of water immersion for geopolymer dosages of 0%, 4%, 8%, and 12%, respectively. Increasing geopolymer dosage effectively improved the resilient modulus of stabilized soil, but did not affect the stress-dependent behavior of stabilized soil. Increasing confining pressure or decreasing deviatoric stress still resulted in a higher resilient modulus for geopolymer stabilized soil.